THE USE COXIB IN NOCICEPTIVE PAIN MANAGEMENT - Eko P, Thomas (Medicina, 2012)
The advent of the Coxibs (COX-2 inhibitor) represented a significant theorical breakthrough in non-steroid anti inflammatory drugs (NSAIDs) treatment. The use of   NSAIDs is limited by by adverse reactions, especially their gastrointestinal (GI) toxicity. The selective COX-2 inhibitors were originally developed to minimize the adverse effect of conventional NSAIDs while maintaining the same analgesic and anti-inflammatory effects. Although the benefit of coxibs  in GI tract has been established the cardiovascular (CV) safety of coxibs still debatable. Several studies have reported an increased incidence of   cardiovascular related morbidity and mortality with the use of COX-2 inhibitor. A definitive answer to whether or not these drugs increase CV risk can only really be derived from multicenter purpose-designed, prospective randomized control trials. Circumstances under which COX-2 selective inhibitor  maybe appropriate are in patients at high GI risk and in patients who did not respond to multiple conventional NSAIDs. Health care providers must consider the efficacy, GI and CV risks, concomitant medications and costs when determining the appropriateness of COX-2 selective inhibitor therapy.(MEDICINA 2012;43:23-30).